Vídeo como recurso didático: qual sua eficiência? - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This work aims to evaluate the use of an audiovisual resource in the construction of knowledge in physics, chemistry and biology to high school students in an interdisciplinary way, through the construction of a documentary. The information transmitted was associated with the current period of the Covid-19 pandemic, as well as other events, which arose during historical events, and which shared the same need for protective measures. The information transmitted covered biological cell content, disinfectant asepsis mechanisms and projectile launching. The assessment was carried out by applying an online questionnaire with open questions, created in Google Forms and answered, before and after the video exhibition, by students from three high school classes, one first-year class and two third-year classes, from a public school, located in the city of Santarém-PA. We emphasize the recommendations during the pandemic period, which contribute to the promotion of health and quality of life, through important and necessary information, to be shared not only in pandemic times.
Keywords: Recurso audiovisual; Interdisciplinaridade; Pandemia; CNPQ:: CIÊNCIAS BIOLÓGICAS